(untitled) (International Journal of Nursing Care, 2020)
Purpose: The project aimed to examine the effects of an existing oral care protocol & practices of nurses on oral assessment scores in ventilated patients. Materials and Methods: Clinical data were collected during intensive care admission after 3 days of implementing an existing oral care protocol in Medical ICU. The Beck Oral Assessment Scale (BOAS) was used to assess the oral cavity and to check the effectiveness of oral care provided by the nurses. Developed the oral care education program consisted of instructions and a clear procedure outlining oral care. Data was input into and analyzed using Microsoft Excel. Results: The existing oral care protocol was found to be effective through the scores on BOAS. The findings revealed areas needs improvement in practices of nurses. The oral care education programme was planned and presented to all nurses working in Medical ICU. Scores on the BOAS differed significantly before and after educational intervention. Resources needed to carry out the protocol were identified and those were provided. Conclusion: Though the protocol of oral care is in place, there is always room for improvement. Oral assessment scores improved after reinforcement training as oral care practices were improved.